XploRe Quantlet Client: Web Service for Mathematical and Statistical Computing - Heiko Lehmann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Many mathematical and statistical questions require the use of computational assistance. The proposed XploRe Quantlet Client (XQC) with it's combined CUI and GUI interface gives access to the XploRe software environment (XploRe Quantlet Server - XQS) with it's large number of available mathematical and statistical methods (Quantlets) via the Internet. To offer the client to a large community the Java language is used to implement the client's functionalities.
urn:nbn:de:kobv:11-10050233
Keywords: 330; Web services; User Interface; Net based mathematical and statistical computing; Client/Server architecture; Java; XploRe; www.xplore-stat.de/java; Statistische Methodenlehre; Client-Server-System; Internet; PC-Software